Better patients' treatment experiences are associated with better postoperative results in Dupuytren's disease. (October 2018) - Poelstra, Ralph; Selles, Ruud W.; Slijper, Harm P.; van der Oest, Mark J.W.; Feitz, Reinier; Hovius, Steven E.R.; Porsius, Jarry T.; ,
This prospective study investigates the extent to which a better experience with healthcare delivery is associated with better postoperative treatment outcomes after surgery for Dupuytren's contracture. Patients undergoing limited fasciectomy or percutaneous needle fasciotomy for Dupuytren's contractures completed the Michigan Hand Outcomes Questionnaire before and 3 months after surgery, together with a patient reported experience measure, while hand therapists assessed the straightness of the finger with a goniometer. Regression analyses were used to examine associations. We found that a better experience with healthcare delivery was associated with better patient-reported outcomes, while association with residual extension deficit was minimal. Strongest associations were seen with communication of the physician, postoperative care and information about the treatment. Experience with the treatment explained up to 12% of the variance in treatment outcome. These findings suggest that patient reported treatment outcomes in Dupuytren's disease can be improved by improving the treatment context. Level of evidence: II